Who Is Coming to Get You? Death-Scene narratives and Illustrations from early Medieval England - Loredana Teresi (Filologia Germanica, 2024)
This article compares textual narratives of the going-out of souls from the body at death, circulating in early medieval England, with visual representations of similar post-mortem scenes featuring in manuscript illustrations. Around twenty images on the topic have emerged from the survey. They appear to be a reflection of their textual counterparts, insomuch as they present the same variety and can be associated to the various traditions circulating in England and on the continent, and which can be ultimately traced back to apocryphal Eastern texts. In literature, two main types of post-mortem death scenes can be found: a type presenting a struggle for the soul that can be associated with such texts as the Visio Pauli,  and a type where the soul is received only by the appropriate band of psychopomps (either angels or devils) on the basis of the moral quality of the dead, as can be seen, for example, in the accounts deriving from the “Macarian legend”. The iconography follows both traditions, although the “Macarian” prejudgement appears prevalent.